Analisis Isi Buku Matematika Kurikulum 2013 SMP Kelas VIII Semester 1 Berdasarkan Taksonomi Timss - Mawarni, Yuyun Evi; , Prof. Budi Murtiyasa, M. Kom; , Dr. Ahcmad Fathoni, M. Pd (2016)
The purpose of this research are: 1) To determine the composition of the material in the book of mathematics curriculum in 2013 junior class VIII Semester 1 domain in terms of content based on taxonomies TIMSS; 2) To determine the composition of the material in the book of mathematics curriculum in 2013 junior class VIII Semester 1 in terms of the cognitive domain based taxonomy TIMSS; 3) To determine the composition of matter of the mathematics curriculum guide 2013 junior class VIII Semester 1 domain in terms of content based on taxonomies TIMSS; 4) To determine the composition of matter of the mathematics curriculum guide 2013 junior class VIII Semester 1 in terms of the cognitive domain taxonomy based on TIMSS. This research is content analysis to analyze the research data of the mathematics curriculum contents of the book in 2013 junior class VIII semester of 1 corresponds to the dimensions of the content and the cognitive dimension based taxonomy TIMSS. The results showed that the analysis of the presentation of the material in terms of the proportion of each content domain, domain algebra occupy the highest proportion with a percentage of 50%, the domain geometry with 33.33% while the percentage of domain data and opportunities with a percentage of 16.67% and there is no question that including in the domain of numbers. Judging from the cognitive dimensions, most of which are applying knowing domain (68.42%) and knowing (21.05%) while the reasoning domain has the lowest percentage is 10.53%. For analytical presentation of questions in terms of the proportion of each dimension of the content, the material has a percentage of 60.64% algebra, geometry material has persetase 32.13% while the material data and the opportunity to have a percentage of 7.23%. If the terms of the cognitive dimension to training issues, from 212 questions were analyzed gained 36 matter only reached the level of cognitive domain knowing the percentage of 16.98%, about 114 have reached the level of cognitive domain applying the percentage of 53.77% and 62 about already reached a level of cognitive reasoning domain with a percentage of 29.25% .Exercises on the domain of knowing, cognitive aspects contained recall is 33.72%, classify/order 24.42%, 23.26% compute, retrieve 11.63% and Recognize 6.98%. For questions on applying domain, cognitive aspects Determine which contained 37.93%, 33.91% and represent implement / model of 28.16%. As for the problems in the domain reasoning, cognitive aspects are contained analyze 36.56%, integrated / synthesize 24.73%, 19.35% justify, Evaluate 11.83%, 5.38% Draw Conclusions and generalize 2.15%.